Оптимізація технологічних параметрів віброкавітаційної обробки рідинних субстанцій - Шевчук, Л. І.; Афтаназів, І. С.; Строган, О. І. (Видавництво Львівської політехніки, 2011)
Описано вібраційний кавітатор, призначений для ініціювання і активації хіміко-технологічних та очисних процесів, зокрема біологічного знезараження води. Робота кавітатора здійснюється у неперервному режимі подачі рідини із продуктивністю понад 5,5 м3/год. Two-stroke oscillation electromagnetic kavitator of resonance action consists of two electromagnets, resilient system, which connects their stators and anchors, and the causative agents of kavitejhen located in a liquid as two sounding boards with opening which hesitate in antifaza. The degree of biological disinfestations of water provides high at her continuous serve with the productivity by about 5,5 м3/hours.